Um estudo histórico-crítico do currículo referência de Minas Gerais: o lugar do ensino de filosofia no ensino médio - Bonacini, André Luis Augusto (Universidade Federal de São Carlos, 2026)
The teaching of Philosophy in Brazilian basic education is characterized by a historical trajectory marked by discontinuities and political disputes concerning curriculum and human formation. In the contemporary context, the implementation of the National Common Curricular Base (BNCC) and the reform of upper secondary education established by Law No. 13.415/2017 has reshaped curricular organization through the centrality of competencies and skills, producing direct impacts on the permanence and epistemological specificity of Philosophy teaching. Within this scenario, this dissertation aims to critically analyze the teaching of Philosophy in the Minas Gerais Reference Curriculum, investigating to what extent this document contributes to the implementation of a systematic and historically grounded philosophical education, or whether it reinforces an instrumental and adaptive conception of schooling. This is a qualitative study of a theoretical-documentary nature, grounded in historical-dialectical materialism as the methodological approach and in Historical-Critical Pedagogy as the theoretical framework. The analyzed sources include the BNCC, relevant educational legislation, and the Minas Gerais Reference Curriculum, as well as specialized literature on curriculum, Philosophy teaching, and contemporary educational policies. The results indicate that, although the Minas Gerais curriculum employs discourses related to integral education and critical thinking, its structure is strongly subordinated to the competency-based approach, which tends to fragment philosophical content and dilute the epistemological specificity of Philosophy. It is concluded that the Minas Gerais Reference Curriculum presents significant limits to the realization of Philosophy teaching consistent with the principles of Historical-Critical Pedagogy, requiring from teachers mediating and resistant practices to ensure the centrality of philosophical knowledge and omnilateral human formation. In accordance with the professional nature of the Professional Master’s Degree in Philosophy (Prof-Filo), this research articulates theoretical analysis with the development and implementation of a pedagogical intervention proposal carried out within the context of Basic Education classrooms, aimed at the systematic organization of philosophy teaching through teacher mediation and the centrality of classical philosophical contents. Such intervention seeks to challenge the limits imposed by competency-based logic, highlighting concrete possibilities for the realization of teaching oriented toward critical formation and the appropriation of historically produced philosophical knowledge.
A historical-critical study of the Minas Gerais reference curriculum: the place of philosophy teaching in high school
Keywords: Ensino de Filosofia; Currículo; Pedagogia Histórico-Crítica; Learning philosophy; Curriculum; Historical-Critical Pedagogy; CIENCIAS HUMANAS::FILOSOFIA; 4. Educação de Qualidade